Drawing on the right side of the brain - Edwards, Betty, 1926- (Souvenir Press, 2013)
Drawing on the Right Side of the Brain is the world's most widely used drawing instruction book. Whether you are a professional, a student, or enjoy art as a hobby, Betty Edwards' practical step-by-step guide will give you greater confidence in your ability, deepen your artistic perception and provide a new way to appreciate the way you perceive the world around you. This groundbreaking guide includes: - Expert advice on materials to use and how to record your progress - Specific focus on perceiving edges, spaces and relationships within your drawings - Problem-solving techniques and guidance on continued development of your skills Blending artistic teaching with psychology, Betty Edwards offers a practical grounding in drawing technique with exercises designed to help you utilise the intuitive and creative right side of your brain, dramatically improving your ability to draw.